Muslim Palestine : the ideology of Ḥamās - Nüsse, Andrea, 1963- (Harwood Academic Publishers, 1998)
"In the modern world, the ideology of islamic fundamentalists is of central importance, but it is often distorted or misunderstood by the world media. In this detailed study, Andrea Nusse provides an insightful analysis of the Palestinian Hamas movement's world-view and shows how the theoretical framework developed by thinkers like Hassan al-Banna, Sayyid Qutb and al-Mawdudi is applied to a specific political, social and economic context. It presents the Islamist position towards recent events, such as the Gulf war, the Madrid peace negotiations and the Hebron Massacre and helps to dissipate myths surrounding modern Islamist movements and their overwhelming success as opposition forces in the Islamic world."--Jacket